Prevalence, Risk Factors and Antibiotic Susceptibility Pattern of Shigella spp Isolated from Gastroenteritis Patients attending some Hospitals in Kano State, Nigeria - Sulaiman, M.A.; Aminu, M.; Ella, E.E.; Abdullahi, I.O. (UMYU Journal of Microbiology Research)
Shigella spp are among the major causes of gastroenteritis, some of which have become multidrug resistant (MDR), making the infection a public health threat. The study was aimed at determining the prevalence, risk factors and antibiotic susceptibility pattern of Shigella spp isolated from gastroenteritis patients. A total of 540 stool samples were collected, involving  450 from gastroenteritis patients (GEPs) and 90 from apparently healthy individuals (AHIs). The isolates were identified based on conventional microbiological techniques and their susceptibility patterns were determined by using Kirby-Bauer method. The patients’ information and demographics were obtained by administering questionnaire. The overall prevalence recorded was 0.9%, with 1.1% and 0% in GEPs and AHIs respectively (Odd ratio= 2.246; 95%CI= 0.1225-40.7708 Significance Level = 0.5873). The highest (2.4%) and lowest (0%) prevalence was recorded among patients who presented with diarrhoea and formed stool respectively (p=0.0487). The prevalence was higher among those who presented with bloody stool (23.1%), compared to those whose appeared normal (0.23%) (p=0.00001). Additionally, prevalence of 4.8% and 0% was observed among those who experienced fever and headache respectively, and the observed differences were significant (P=0.0097). However, neither age nor gender was found to be a risk factor. All the isolates were susceptible to augmentin, and 60% of the isolates showed significant Multiple Antibiotic Resistance (MAR) index. It was concluded that the prevalence of shigellosis was comparatively low and most of the patients presented with bloody diarrhoea and fever. Augmentin was the drug of choice and a possible sign of inappropriate use of antibiotics was observed among the subjects.